Effectiveness Soaking Duration of Rice Seed with Trichoderma sp. for Controlling Seed-Borne Pathogenic Fungi - Nur Aini Mahfud; Arika Purnawati; Penta Suryaminarsih (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Low rice productivity due to the use of low-grade seeds. The quality of the seeds can suffer a decrease caused by the attack of pathogenic fungi carried by the seeds both at the time of planting and storage, which will have an impact on the disruption of plant growth. Biopriming using Trichoderma sp. be an effort to control because it is antagonistic to pathogens. The success of biopriming is also influenced by the duration of seed priming. This study aims to examine the duration of soaking rice seeds with Trichoderma sp. the most effective for lowering seed-borne pathogenic infections. The study was conducted by providing seed soaking treatment using Trichoderma sp. suspension for 6 hours, 12 hours, and 24 hours with PDA medium incubation test method and Growing on Test. The parameters tested are the percentage of infection rate and the percentage of germination. Identification results showed that pathogenic fungi carried by seeds included Rhizopus sp., Fusarium sp., Aspergillus sp., and Mucor sp. The results showed the duration of soaking rice seeds with Trichoderma sp. more effective in decreasing the infection rate is at a 24-hour duration. However, the duration of soaking rice seeds with Trichoderma sp. there was no noticeable difference for the percentage parameter of seed germination.